Atmospheric radioactive nuclide deposition on the coast of the Maowei Sea, northern Beibu Gulf, China - Wang, Xilong; Zhou, Jiaodi; Su, Kaijun; Du, Jinzhou; Wei, Longtao; Li, Xing; Du, Juan; Lu, Dongliang (Frontiers in Marine Science, 2023)
The natural radioisotopes 7Be, 210Pb, and 210Po, with different half-lives, are all particle-reactive and serve as natural tracers to study sources and transportation of sediments, sedimentation rates, and sediment chronology. Atmospheric deposition of these radioisotopes is the premise and foundation of their tracing application. The Maowei Sea is a semi-closed bay along the Beibu Gulf, which is an important gulf in the northwest of the South China Sea, but the atmospheric deposition of the abovementioned radioisotopes has not been systematically reported along the coast. In this research paper, the atmospheric depositional fluxes of 7Be, 210Pb, and 210Po were observed over a period from June 2018 to December 2021 on the coast of the Maowei Sea. The annual atmospheric depositional fluxes (Bq m-2 yr-1) of 7Be, 210Pb, and 210Po on the coast of the Maowei Sea were 496.80, 201.72, and 58.08, respectively. The distributions for 7Be and 210Pb depositional fluxes during a whole year (years 2019 and 2021) followed a bimodal pattern, with one peak from February to April and another peak from August to October, while the distribution for 210Po depositional flux showed only one peak during the year of 2019 and another during 2021. The deposition flux and activity of 7Be showed a strong positive correlation with the deposition flux and activity of 210Pb, respectively; the deposition flux and activity of 210Po also showed positive correlations with the deposition fluxes and activities of 210Pb and 7Be, respectively, indicating a similarly scavenging behavior from the atmosphere. A Pearson correlation matrix was used to illustrate the factors influencing the atmospheric depositions and found that precipitation, air quality index (AQI), and PM (both PM2.5 and PM10) were the major factors that influenced the deposition of these three radionuclides. Precipitation had significant positive correlations with the deposition fluxes of all three radionuclides, indicating that, for these radionuclides, rainfall was the main scavenging way from the atmosphere. The observations for specific single rainfall events and their air mass backward trajectory analyses showed that the air masses movement during the rainfall may be another important factor that impacted the depositional fluxes for 7Be, 210Pb, and 210Po.